Medical Doctors' Knowledge of Dental Specialty: Implication for Referral - C.C. Azodo; O. Ehigiator; A.O. Ehizele; O. Ololo (Саратовский научно-медицинский журнал, 2010)
The research goal is to assess Medical Doctors' knowledge of the various dental specialties and to determine if their past dental experience affects their level of knowledge. Resident Doctors and Medical Officers working in the University of Benin Teaching Hospital, Nigeria were surveyed with self-administered questionnaire in 2008. A total of 142 doctors responded to the questionnaire, giving a response rate of 71%. The female: male ratio was approximately 1:2.5. The designations of respondents were Senior Registrar 21.8%, Registrar 48.6% and Medical Officers 29.6%. The Departments that returned the questionnaire were Internal Medicine 21.1%, Surgery 19%, Paediatrics 15.5% Family Medicine 11.3%, Accident and Emergency 5.6%, Radiology 4.9%, Ophthalmology 8.5%, Pathology 5.6%, Anaesthesiology 5.6% and Mental Health 2.8% The mean knowledge score was 10.1±3.3. (Maximum score =21). Only a small percentage (5.6%) had a good knowledge (scored above 16), 79.6% had a fair knowledge (scored 8-15) and 14.8% had a very poor knowledge (scored less than 8). Doctor with history of previous dental treatment had better knowledge (P=0.03). The knowledge of Medical Doctors about the various areas in Dentistry is presently not satisfactory. Comprehensive care of patients, which includes prompt and appropriate referral, can be optimized by improvement of Doctors' knowledge of dental specialty through seminars and other educational interventions